Increased resource use in men with metastatic prostate cancer does not result in improved survival or quality of care at the end of life. Issue 10 (26th March 2018) - Golan, Ron; Bernstein, Adrien N.; Gu, Xiangmei; Dinerman, Brian F.; Sedrakyan, Art; Hu, Jim C.
Abstract : BACKGROUND: Cancer care and end‐of‐life (EOL) care contribute substantially to health care expenditures. Outside of clinical trials, to our knowledge there exists no standardized protocol to monitor disease progression in men with metastatic prostate cancer (mPCa). The objective of the current study was to evaluate the factors and outcomes associated with increased imaging and serum prostate‐specific antigen use in men with mPCa. METHODS: Using Surveillance, Epidemiology, and End Results‐Medicare data from 2004 to 2012, the authors identified men diagnosed with mPCa with at least 6 months of follow‐up. Extreme users were classified as those who had either received prostate‐specific antigen testing greater than once per month, or who underwent cross‐sectional imaging or bone scan more frequently than every 2 months over a 6‐month period. Associations between extreme use and survival outcomes, costs, and quality of care at EOL, as measured by timing of hospice referral, frequency of emergency department visits, length of stay, and intensive care unit or hospital admissions, were examined. RESULTS: Overall, a total of 3026 men with mPCa were identified, 791 of whom (26%) were defined as extreme users. Extreme users were more commonly young, white/non‐Hispanic, married, higher earning, and more educated ( P <.001, respectively). Extreme use was not associated with improved quality of care at EOL. Yearly health care costs after diagnosis were 36.4% higher among extreme users (95% confidence interval, 27.4%‐45.3%; P <.001). CONCLUSIONS: Increased monitoring among men with mPCa significantly increases health care costs, without a definitive improvement in survival nor quality of care at EOL noted. Monitoring for disease progression outside of clinical trials should be reserved for those in whom findings will change management. Cancer 2018;124:2212‐9 . © 2018 American Cancer Society . Abstract : Increased imaging and serum prostate‐specific antigen testing does not improve survival nor quality of care at the end of life. Testing should be reserved for patients for whom findings will change management.